Genome-Wide Identification and Evolutionary Analysis of the SRO Gene Family in Tomato - Li, Ning; Xu, Ruiqiang; Wang, Baike; Wang, Juan; Huang, Shaoyong; Yu, Qinghui; Gao, Jie (Frontiers in Genetics, 2021)
Background: Similar to radical-induced cell death 1, SRO is a family of plant-specific small molecule proteins that play an important role in plant growth and development and environmental responses. However, SROs still lack systematic characterization in tomato. Methods: Based on bioinformatics methods, SRO family genes were identified and characterized from cultivated tomatoes and several wild tomatoes. qRT-PCR was used to study the expression of SRO gene in cultivated tomatoes. Result: Phylogenetic and evolutionary analyses showed that SRO genes in angiosperms share a common ancestor and that the number of SRO family members changed as plants diverged and evolved. Cultivated tomato had six SRO members, five of which still shared some degree of identity with the ancestral SRO genes. Genetic structure and physicochemical properties showed that tomato SRO genes were highly conserved with chromosomal distribution. They could be divided into three groups based on exon-intron structure, and cultivated tomato contained only two of these subclades. A number of hormonal, light and abiotic stress-responsive cis-acting elements were identified from the promoter of the tomato SRO gene, and they also interacted with a variety of stress-responsive proteins and microRNAs. RNA-seq analysis showed that SRO genes were widely expressed in different tissues and developmental stages of tomato, with significant tissue-specific features. Expression analysis also showed that SRO genes respond significantly to high temperature and salt stress and mediate the tomato hormone regulatory network. These results provide a theoretical basis for further investigation of the functional expression of tomato SRO genes and provide potential genetic resources for tomato resistance breeding.